Eating Habits of the To Pekurehua and Javanese Tribes in Central Sulawesi: A Cultural Perspective - Abd. Rauf, Rustam; Malik , Shintami R.; Damayanti , Lien; Rahman, Aulia; Salingkat , Chitra A.; Sultan, Hardiyanti; Erny, Erny (Journal of Health and Nutrition Research, 2025)
Household characteristics are defined by socioeconomic conditions and other factors, including cultural aspects. Culture dictates dietary choices, methods of preparation, locations, and timing of food preparation. This study examined cultural influences on family dietary practices among the To Pekurehua and Javanese tribes. This research was conducted over a ten-month period, from February to November 2023. The application of this equation yielded a sample of 79 respondents from the North Lore District (representing the To Pekurehua tribe) and 41 respondents from the West Pamona District (representing the Javanese tribe). The To Pekurehua and Javanese tribes possessed average meal frequencies of 2.86 and 3.00 times each day, respectively. The practice of communal dining was observed in 91.1% of the To Pekurehua tribe and 87.8% of the Javanese tribe. The To Pekurehua tribe generated a family dinner participation rate of 87.3%, whereas the Javanese tribe’s rate was 82.9%. In both tribes, fathers, as the head of the household, received priority in food distribution. In contrast, the wives in the Javanese tribe exerted greater influence over the food menu than those in the To Pekurehua tribe.